2020
DOI: 10.21873/anticanres.14349
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Occult Blood Tests in Colorectal Cancer Screening: Systematic Review and Meta-analysis of Traditional and New-generation Fecal Immunochemical Tests

Abstract: Background/Aim: Noninvasive fecal occult blood tests (FOBTs) are recommended by current guidelines for colorectal cancer (CRC) screening. Our aim was to assess the diagnostic performance of traditional guaiac-based FOBTs (gFOBT) and new-generation immunochemical FOBTs (iFOBT) in CRC screening by carrying out a systematic review and meta-analysis. Patients and Methods: PubMed, Embase, Cochrane Library, and Web of Science were searched for eligible articles published before February 17, 2020. Three independent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 10 publications
3
50
0
1
Order By: Relevance
“…A previous meta-analysis comparing different colorectal screening techniques also found a higher diagnostic yield of colorectal neoplasia with endoscopic screening when compared with fecal tests [13]. However, that data was based predominantly on gFOBT which have been found to be inferior to FITs [15,16]. Also, in their analysis, endoscopic screening comprised of both flexible sigmoidoscopy and colonoscopy, such that a direct comparison of sigmoidoscopy with FIT was not possible.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous meta-analysis comparing different colorectal screening techniques also found a higher diagnostic yield of colorectal neoplasia with endoscopic screening when compared with fecal tests [13]. However, that data was based predominantly on gFOBT which have been found to be inferior to FITs [15,16]. Also, in their analysis, endoscopic screening comprised of both flexible sigmoidoscopy and colonoscopy, such that a direct comparison of sigmoidoscopy with FIT was not possible.…”
Section: Discussionmentioning
confidence: 95%
“…Flexible sigmoidoscopy has been shown to have similar efficacy to colonoscopy in identifying left-sided lesions with a reduction in incidence and mortality rates by 25% and 30% respectively, when compared to no screening or usual care [7][8][9][10][11]. Fecal immunochemical test has been reported to have better sensitivity than gFOBT in detecting CRCs and advanced adenomas and has largely replaced gFOBT as the fecal test of choice [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been shown that the faecal immunochemical test (FIT) is a tool that makes it possible to identify patients at the highest risk of CRC among those with symptoms [9,10]. FIT is a non-invasive test, which detects faecal haemoglobin concentrations (f-Hb), and has a high diagnostic accuracy for CRC [10][11][12], higher than that of the SIGN or NICE criteria [13] and traditional guaiac based faecal occult blood tests [14]. This test, with high sensitivity and specificity is essential for early detection and avoidance of unnecessary invasive tests.…”
Section: Introductionmentioning
confidence: 99%
“…In a population-screening context, the FIT has a sensitivity of 86% and a specificity of 85% to detect CRC [16] and a sensitivity of 29% and a specificity of 97% to detect advanced adenoma [17]. Thus, the FIT is much less sensitive for advanced adenomas.…”
Section: Diagnostic Accuracy Of Faecal Immunochemical Tests In Crc Screeningmentioning
confidence: 99%